A multiple case study of inclusive learning communities enabling active participation in geoscience field courses for students with physical disabilities. Issue 4 (2nd October 2019) - Atchison, Christopher L.; Marshall, Anita M.; Collins, Trevor D.
Abstract: This article presents a multiple case study exploring the emergence of inclusive learning communities within geoscience field courses designed to enable the active participation of students with disabilities. The purpose is to reflect on the outcomes of three distinct projects and consider what lessons can be drawn from them to help promote and inform the development of inclusive teaching and learning. Drawing from established research on learning communities, a set of core practices are applied as an analytical framework to review student and staff experiences across a range of inclusive field experiences. This cross-case comparison provides critical insights into the instructional strategies for the inclusion of students with disabilities in geoscience field courses. Specifically, this work demonstrates the importance of establishing inclusive learning communities through meaningful site selection, fostering social inclusion, and using technology to mediate access and facilitate collaboration in field-based teaching and learning.